Traditional games to increase participation in recreational-sports activities in the "Raposo" Community - Tatiana Lobaina-Capdesuñer; Eusebia Isaac-Noa (Universidad de Guantánamo, 2019)
In the "Raposo" Community, of the West Central Popular Council of Guantanamo municipality, there is an insufficient incorporation of its inhabitants in the recreational activities offered in this area. Through a diagnosis it was found that the difficulties were in an insufficient recreational offer. In this research is proposed a set of traditional games, which will increase the incorporation of the population to the activities offered. Methods of the theoretical, empirical and mathematical level were used. The proposal was highly accepted, thus meeting the proposed objective by incorporating a greater number of people into the activities.